The Foundations of the 15th Century Indian Economy According to Nicolo Conti's Records - Uygur, Türker (Fırat University, 2026)
India has attracted attention of many civilizations throughout history due to its geographical location, favorable living conditions, and resources. The shifting political and military power dynamics over time have enabled the settlement of diverse ethnic, social, religious, and cultural groups in the region. One of the most important factors affected by this has undoubtedly been India's economic situation. It is seen that 15th century was a period when India's economic, social, and cultural structure was generally shaped. Records of various eastern and western travelers also support this view. Nicolo de Conti, a Venetian merchant and traveler, started to engage in trade at a young age and made numerous expeditions to discover the riches of the East. Among these, the one that made his name recorded in history was his trip to India and his accounts. These records provide very significant information about economic, social, and cultural structure of 15th century India. In this study, economic structure of the period and its foundations were examined based on Conti’s records. It was revealed that diversity originating from climatic, locational, and demographic density in the vast geography of India led to regional differences in terms of economic foundations and these differences were analyzed.

Hindistan coğrafi konumu, uygun yaşam koşulları ve sahip olduğu zenginlikler sebebiyle tarih boyunca birçok medeniyetin dikkatini çekmiştir. Dönem dönem değişen siyasi ve askeri güç dengeleri etnik, sosyal, dini ve kültürel bakımdan farklı insan guruplarının bölgeye yerleşmesine imkan sağlamıştır. Bu durumun etkilediği en önemli unsurlardan biri de hiç şüphesiz Hindistan’ın ekonomik durumu olmuştur. XV. yüzyılın Hindistan’ın ekonomik, sosyal ve kültürel yapısının genel manada şekillendiği bir dönem olduğu görülmektedir. Doğulu ve batılı birçok seyyahın kayıtları da bu görüşü destekler niteliktedir. Venedikli bir tüccar ve seyyah olarak bilinen Nicolo de Conti, genç yaşta ticaretle uğraşmaya başlamış ve doğunun zenginliklerini keşfetmek üzere çeşitli seyahatler yapmıştır. Bunlar arasında onun adının tarihe geçmesini sağlayacak olanı ise hiç şüphesiz Hindistan seyahati ve buna dair anlattıkları olmuştur. Bu kayıtlar XV. yüzyıl Hindistan’ının ekonomik, sosyal ve kültürel yapısı hakkında oldukça önemli bilgiler içermektedir. Bu çalışmada, Conti’nin tutmuş olduğu kayıtlar üzerinden dönemin ekonomik yapısı ve dayandığı temeller incelenmiştir. Conti’nin kayıtlarından Hindistan’ın geniş coğrafyasındaki iklimsel, konumsal ve demografik yoğunluk kaynaklı çeşitliliğin ekonomik dayanaklar noktasında bölgesel farklılıklara yol açtığı görülmüş ve bu farklılıklar üzerine bir değerlendirme yapılmıştır.
Nicolo Conti’nin Kayıtlarına Göre XV. Yüzyıl Hindistan Ekonomisinin Dayandığı Temeller
Keywords: Medieval Asian History; Ortaçağ Asya Tarihi; Medieval European History; Ortaçağ Avrupa Tarihi; Medieval Cities; Ortaçağ Kentleri